A INTEGRAÇÃO ENTRE O PLANEJAMENTO E O ORÇAMENTO PÚBLICO NAS INSTITUIÇÕES FEDERAIS DE ENSINO SUPERIOR: UM ESTUDO DE CASO MÚLTIPLO - Francisco, Jailton Gonçalves (2005)
The main purpose of this study is to investigate the integration of the public planning and budget at Public Universities, according to the managers perception of the institution; it also aims at identifying , for each of the analyzed aspects, the importance of the budget as an instrument of planning and resources location. It has tried to correlate an investigated conceptual basis with a field research, to extract inferences about the topic. A structured form with closed questions has been used with the aim of obtaining the perception from managers that are responsible for the Public Universities PU planning area. The research has been applied to those institutions, 55 PU in total, obtaining 41 answers to the form. It has verified that the people who replied the form notice that, although the budget be an important instrument of integration with planning, it cannot reflect the real needs of the involved community and, to have a better utilization of the resources, it needs to prioritize them by an Institutional Development Plan IDP.